2020
DOI: 10.1186/s12888-020-02779-7
|View full text |Cite
|
Sign up to set email alerts
|

Are diabetes self-management programmes for the general diabetes population effective for people with severe mental illness?: a systematic review

Abstract: Background Diabetes self-management education programmes are effective in improving health outcomes in the general population with diabetes. However, it is not known if these programmes include people who also have a severe mental illness (SMI) and, if so, what their outcomes are. The aim of this review was to examine if evaluations of diabetes self-management education programmes included people with SMI, and if so, whether the interventions were beneficial for this population. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Previous intervention studies have shown that pharmacological and behavioral interventions have a positive impact on individuals with severe psychiatric disorders (43). However, little is known regarding prevention of type 2 diabetes in individuals with a psychiatric disorder (44), which is partially due to the fact that individuals with psychiatric disorders are often excluded from traditional intervention studies, and our knowledge regarding the effect of intervention and preventions studies in this population is limited (45). Our findings also highlight the importance of focusing on prevention of type 2 diabetes in the population of individuals with a psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Previous intervention studies have shown that pharmacological and behavioral interventions have a positive impact on individuals with severe psychiatric disorders (43). However, little is known regarding prevention of type 2 diabetes in individuals with a psychiatric disorder (44), which is partially due to the fact that individuals with psychiatric disorders are often excluded from traditional intervention studies, and our knowledge regarding the effect of intervention and preventions studies in this population is limited (45). Our findings also highlight the importance of focusing on prevention of type 2 diabetes in the population of individuals with a psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the efficacy of non-pharmacological interventions to improve clinical outcomes such as average blood glucose levels (HbA1c), diabetes self-management, and quality of life in the general T2D adult population reports inconsistent findings [ 22 23 ]. Existing interventions have largely been tested with people without SMI; people with SMI are not always specified in studies, or are excluded in reviews [ 24 25 ], making it impossible to generalise these findings to adults with comorbid T2D and SMI [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of these many barriers, people with SMI might find it difficult to effectively engage with physical health self-management programmes designed for people without SMI. People with SMI also tend to be excluded from trials assessing effectiveness of these programmes [ 17 ]. This points to the need for more tailored interventions that target the challenges people with SMI experience in relation to their self-management [ 18 ].…”
Section: Introductionmentioning
confidence: 99%